Creep of face-centered-cubic 111 and 100 grains in FeCoNiCrMn and FeCoNiCrMnAl alloys: Orientation and solid solution effects. (December 2018) - Tsai, M.T.; Huang, J.C.; Lin, P.H.; Liu, T.Y.; Liao, Y.C.; Jang, Jason S.C.; Song, S.X.; Nieh, T.G.
Abstract: In this study, creep behavior of the face-centered-cubic (FCC) 111 and 100 grains in single-phase Fe20 Co20 Ni20 Cr20 Mn20 and dual-phase Fe18 Co18 Ni20 Cr18 Mn18 Al8 high-entropy alloys (HEAs) was evaluated using a nanoindentation method over temperatures range of 300–600 °C. We measured the creep response of the two different grain orientations in the two alloys in order to study the orientation and solid-solution effects. Creep stress exponent (∼3.8–5.0) and activation energy (240–260 kJ/mol) were extracted and analyzed from stain rate-stress and stain rate-temperature data to provide information on the creep mechanism. The results indicated that creep was controlled by dislocation climb in both alloys at both orientations. However, we pointed out that, based upon activation energy value alone, it was difficult to identify which elemental constituent would be the dominant diffusing species responsible for vacancy diffusion during the climb. It was found that creep activation volume for the current two HEAs (140 Å 3 or ∼12Ω, where Ω is the atomic volume) at 600 °C is larger than that reported for the Ni-based superalloys (∼50–100 Å 3 or less) within a similar temperature range. The significance of this larger activation volume is also discussed. Graphical abstract: Highlights: Nanoindentation creep responses in high entropy alloys are examined over 300–600 °C. The extracted activation energy under the constant stress condition is around 260 kJ/mol. The current high entropy alloys possess relatively large volume about 140 Å 3 at 600 °C.